Preparation process of nylon 66

Through the method of reasonable proportioning and multi-stage continuous reactor reaction in the nylon 66 preparation process, the problem of insufficient performance of traditional nylon 66 materials in extreme environments is solved, and the performance improvement of nylon 66 composite materials is achieved, achieving high performance and environmental protection , safe materials.

CN119391178APending Publication Date: 2025-02-07ZHONGPING SHENMA JIANGSU NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411600487.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional nylon 66 materials show insufficient dimensional stability, mechanical properties and durability in extreme environments such as high temperature, high pressure and chemical corrosion, making it difficult to meet the modern industry's demand for high-performance engineering plastics.

Method used

A nylon 66 preparation process is adopted, and the ratio of adipic acid, hexanediamine, modified glass fiber, rubber toughening agent, nanosilicon dioxide, plasticizer, flame retardant and antioxidant is reasonable, and the Multi-stage continuous reactors react to form synergistic effects to improve material performance.

Benefits of technology

It significantly improves the mechanical properties, toughness, thermal stability, flame retardancy and processability of nylon 66 composite materials, solves the problems existing in the performance and processing of traditional nylon 66 materials, and obtains a high-performance, environmentally friendly and safe Nylon 66 composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a preparation process of nylon 66. The preparation process comprises the following steps: S1, drying adipic acid and hexamethylenediamine; s2, glass fiber pretreatment: carrying out surface modification in a reaction kettle through a coupling agent to obtain modified glass fiber; s3, adding adipic acid, hexamethylenediamine and a catalyst into the reaction kettle, heating to 240-260 DEG C under the protection of nitrogen, and carrying out condensation polymerization; s4, after the polycondensation reaction is finished, gradually adding the rubber flexibilizer, the nano silicon dioxide, the plasticizer, the flame retardant and the antioxidant into the reaction kettle, and blending; s5, reacting the reaction material in a multi-stage continuous reactor to obtain nylon 66; and S6, carrying out heat treatment on the nylon 66, cooling, and pelletizing. The mechanical property, toughness, thermal stability, flame retardance and processability of the nylon 66 composite material are comprehensively improved, the problems existing in the performance and processing process of a traditional nylon 66 material are effectively solved, and finally the high-performance, environment-friendly and safe nylon 66 composite material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nylon, and in particular to a preparation process of nylon 66. Background Art

[0002] With the rapid development of industry, high viscosity nylon 66 materials have been widely used in many fields. For example, in the field of automobile manufacturing, high viscosity nylon 66 can be used to produce lighter and more durable parts due to its excellent mechanical strength and heat resistance, thereby effectively reducing the overall weight of the vehicle and improving fuel efficiency. In the electronics industry, due to its excellent insulation properties and high thermal stability, high viscosity nylon 66 has become an ideal choice for making high-performance electronic component packaging materials, which can meet stringent insulation and heat dissipation requirements.

[0003] However, the performance of traditional nylon 66 materials has gradually failed to meet the application requirements of these special fields. Especially in extreme environments such as high temperature, high pressure and chemical corrosion, the dimensional stability, mechanical properties and durability of traditional nylon 66 are insufficient, which affects its further promotion and application in these fields.

[0004] Therefore, it is particularly important to develop a nylon 66 material with higher viscosity, better mechanical properties and stronger environmental resistance. This can not only significantly improve the material's resistance to high temperature and chemical corrosion, but also improve its stability and service life in extreme environments, thereby meeting the growing demand of modern industry for high-performance engineering plastics. Summary of the invention

[0005] The invention discloses a nylon 66 preparation process, which is used to solve relevant technical problems in the background technology.

[0006] The technical solution provided by the present invention is as follows: A nylon 66 preparation process comprises the following steps:

[0007] S1, taking adipic acid and hexamethylenediamine and drying them;

[0008] S2, pre-treating the glass fiber, performing surface modification by using a coupling agent in a reaction kettle to obtain modified glass fiber;

[0009] S3, adding adipic acid, hexamethylenediamine and a catalyst into a reaction kettle, and heating to 240-260° C. under nitrogen protection to carry out polycondensation reaction;

[0010] S4. After the polycondensation reaction is completed, the rubber toughening agent, nano-silicon dioxide, plasticizer, flame retardant and antioxidant are gradually added into the reaction kettle for blending;

[0011] S5, reacting the reaction materials in a multi-stage continuous reactor to obtain nylon 66;

[0012] S6. Heat treat nylon 66, cool it, and pelletize it.

[0013] In one embodiment, the ratio of adipic acid, hexamethylenediamine, modified glass fiber, rubber toughening agent, nano-silica, plasticizer, flame retardant, antioxidant and catalyst is: adipic acid: 50-55 parts, hexamethylenediamine: 45-50 parts, modified glass fiber: 20-30 parts, rubber toughening agent: 5-10 parts, nano-silica: 1-5 parts, plasticizer: 1-3 parts, flame retardant: 3-8 parts, antioxidant: 0.5-2 parts, catalyst: 0.1-0.5 parts.

[0014] In one embodiment, the coupling agent is γ-aminopropyltriethoxysilane.

[0015] The process for preparing nylon 66 according to claim 1, characterized in that step S2 further comprises:

[0016] S201, soaking the glass fiber in deionized water, stirring to remove dust and impurities on the surface, further cleaning with a neutral detergent to remove surface oil and other organic matter, and drying the cleaned glass fiber in an oven at 80-100° C. for 2-3 hours to ensure that the water is completely evaporated;

[0017] S202, dissolving the coupling agent in 95% ethanol or deionized water at a mass ratio of 3-5%, adding a small amount of acetic acid to adjust the pH to 4-5, and mixing evenly;

[0018] S203 completely immerses the glass fiber in the coupling agent solution for 0.5-1h to ensure that the fiber surface is completely covered by the coupling agent;

[0019] S204, drying the impregnated glass fiber at 80-120°C for 1-2h, then curing at 150°C for 0.5-1h, and finally cooling the cured glass fiber to room temperature to obtain modified glass fiber.

[0020] In one embodiment, in the polycondensation reaction in step S3, the pressure in the autoclave is controlled at 1-2 MPa, the reaction time is 4-6 h, and the generated water is continuously discharged.

[0021] In one embodiment, step S4 further comprises: first adding a rubber toughening agent, and then sequentially adding nano silicon dioxide, a plasticizer, a flame retardant and an antioxidant, and slowly adding them within 1-5 minutes.

[0022] In one embodiment, in step S4, the blending time is 0.5 h, the stirring speed is 50-100 rpm, and the temperature is maintained at 260° C.-270° C.

[0023] In one implementation, step S5 further includes:

[0024] S501, placing the reaction materials into the first reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.1-0.5MPa, the stirring speed is 50-100 rpm, and the reaction time is 0.5-1h;

[0025] S502, the reaction materials enter the second reaction unit of the reactor, the reaction temperature is 270°C-280°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 30-60 rpm, and the reaction time is 0.5-1h;

[0026] S503, the reaction materials enter the third reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 20-40 rpm, and the reaction time is 0.5-1h.

[0027] The process for preparing nylon 66 according to claim 1, characterized in that step S6 further comprises:

[0028] S701, keep nylon 66 between 180℃-200℃, and heat treatment for 1-2h;

[0029] S702, cooling the heat-treated nylon 66 to room temperature;

[0030] S703, after cooling, the nylon 66 is pelletized with a particle diameter of 3-5 mm.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The present invention achieves a comprehensive improvement in material performance by combining adipic acid, hexamethylenediamine, modified glass fiber, rubber toughening agent, nano-silicon dioxide, plasticizer, flame retardant and antioxidant in a reasonable proportion and acting together in a nylon 66 matrix to form a synergistic effect between the components.

[0033] First, the modified glass fiber is surface-modified by γ-aminopropyltriethoxysilane coupling agent, and forms stable chemical bonds with the amino and carboxyl groups in the nylon 66 matrix during the polycondensation reaction. The formation of this chemical bond significantly enhances the interfacial bonding between the glass fiber and the nylon 66 matrix, reduces stress concentration at the interface, and thus improves the overall mechanical properties of the composite material, especially tensile strength and rigidity.

[0034] Secondly, the rubber toughening agent is evenly dispersed in the nylon 66 matrix during the blending process, forming a flexible network through physical block or chemical cross-linking. This flexible network can effectively absorb and disperse external stress when impacted, thereby significantly improving the toughness and impact resistance of the material and avoiding brittle fracture of the material under high load conditions.

[0035] At the same time, nano-silicon dioxide, with its high specific surface area and chemical activity, forms a uniform dispersion in the nylon 66 matrix and forms multi-point bonding with the matrix. This bonding not only effectively fills the microscopic defects inside the material, restricts the movement of polymer segments, improves the rigidity and wear resistance of the material, but also enhances the thermal stability of the material through synergistic effects, making it have better performance at high temperatures.

[0036] In addition, the introduction of plasticizers effectively reduces the glass transition temperature of nylon 66, improves the flexibility and processing fluidity of the material, and ensures a smooth and efficient process. Flame retardants significantly improve the flame retardancy of the material and slow down the flame propagation speed by combining with the molecular chain of nylon 66. Antioxidants play a role in capturing free radicals and inhibiting thermal oxidation reactions in the material, significantly extending the service life of the material and improving the stability and environmental performance of long-term use.

[0037] Through the synergistic effect of the above components, the present invention achieves comprehensive improvement in the mechanical properties, toughness, thermal stability, flame retardancy and processability of the nylon 66 composite material, effectively solves the problems existing in the performance and processing of traditional nylon 66 materials, and finally obtains a high-performance, environmentally friendly and safe nylon 66 composite material.

[0038] (2) In the present invention, after passing through the multi-stage continuous reactor, the nylon 66 molecular chain is fully extended to achieve the expected high molecular weight and high viscosity; the reaction materials are uniform, and by-products such as moisture and volatile substances are effectively removed, ensuring the purity and performance consistency of the polymer; at the same time, the multi-stage reactor can effectively control the reaction conditions at each stage, ensure the full progress of each step of the reaction, reduce the accumulation of intermediate products, and improve production efficiency. DETAILED DESCRIPTION

[0039] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0040] Example 1

[0041] A nylon 66 preparation process comprises the following steps:

[0042] S1, taking adipic acid and hexamethylenediamine and drying them;

[0043] S2, putting glass fiber into a reactor, the glass fiber is short chopped glass fiber, the length of which is 3-6 mm, and the diameter of which is 10-20 microns, and putting a coupling agent into the reactor to modify the surface of the glass fiber, to obtain 20 parts of modified glass fiber;

[0044] S201, soaking the glass fiber in deionized water, stirring to remove dust and impurities on the surface, further cleaning with a neutral detergent to remove surface oil and other organic matter, and drying the cleaned glass fiber in an oven at 80-100° C. for 2-3 hours to ensure that the water is completely evaporated;

[0045] S202, dissolving γ-aminopropyltriethoxysilane in 95% ethanol or deionized water at a mass ratio of 3-5%, adding a small amount of acetic acid to adjust the pH to 4-5, and mixing evenly; the solution pH needs to be maintained between 4-5 to avoid excessive acidity or alkalinity that may cause fiber damage or coupling agent failure;

[0046] S203 completely immerses the glass fiber in the coupling agent solution for 0.5-1h to ensure that the fiber surface is completely covered by the coupling agent;

[0047] S204, drying the impregnated glass fiber at 80-120° C. for 1-2 h, then curing at 150° C. for 0.5-1 h, and finally cooling the cured glass fiber to room temperature to obtain a modified glass fiber;

[0048] S3, adding 50 parts of adipic acid, 50 parts of hexamethylenediamine and 0.1 parts of catalyst into the reaction kettle, heating to 240-260°C under nitrogen protection for polycondensation reaction, controlling the pressure in the kettle at 1-2MPa during the polycondensation reaction, the reaction time is 4-6h, and the generated water is continuously discharged; wherein the catalyst is ammonium dihydrogen phosphate;

[0049] S4. After the polycondensation reaction is completed, 5 parts of rubber toughening agent, 1 part of nano-silicon dioxide, 1 part of plasticizer, 3 parts of flame retardant and 0.5 part of antioxidant are gradually added into the reaction kettle for blending. The blending time is 0.5h, the stirring speed is 50-100 rpm, and the temperature is maintained at 260°C-270°C; wherein the rubber toughening agent is polybutadiene, the plasticizer is phthalate, the flame retardant is aluminum hydroxide, and the antioxidant is tert-butyl hydroxytoluene;

[0050] S5, reacting the reaction materials in a multi-stage continuous reactor to obtain nylon 66;

[0051] S501, placing the reaction materials into the first reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.1-0.5MPa, the stirring speed is 50-100 rpm, and the reaction time is 0.5-1h;

[0052] S502, the reaction materials enter the second reaction unit of the reactor, the reaction temperature is 270°C-280°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 30-60 rpm, and the reaction time is 0.5-1h;

[0053] S503, the reaction materials enter the third reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 20-40 rpm, and the reaction time is 0.5-1h;

[0054] S6, heat-treating nylon 66, cooling, and pelletizing;

[0055] S701, keep nylon 66 between 180℃-200℃, and heat treatment for 1-2h;

[0056] S702, cooling the heat-treated nylon 66 to room temperature;

[0057] S703, after cooling, the nylon 66 is pelletized with a particle diameter of 3-5 mm.

[0058] Example 2

[0059] A nylon 66 preparation process comprises the following steps:

[0060] S1, taking adipic acid and hexamethylenediamine and drying them;

[0061] S2, putting glass fiber into a reactor, the glass fiber is short chopped glass fiber, the length of which is 3-6 mm, and the diameter of which is 10-20 microns, and putting a coupling agent into the reactor to modify the surface of the glass fiber, to obtain 30 parts of modified glass fiber;

[0062] S201, soaking the glass fiber in deionized water, stirring to remove dust and impurities on the surface, further cleaning with a neutral detergent to remove surface oil and other organic matter, and drying the cleaned glass fiber in an oven at 80-100° C. for 2-3 hours to ensure that the water is completely evaporated;

[0063] S202, dissolving γ-aminopropyltriethoxysilane in 95% ethanol or deionized water at a mass ratio of 3-5%, adding a small amount of acetic acid to adjust the pH to 4-5, and mixing evenly;

[0064] S203 completely immerses the glass fiber in the coupling agent solution for 0.5-1h to ensure that the fiber surface is completely covered by the coupling agent;

[0065] S204, drying the impregnated glass fiber at 80-120° C. for 1-2 h, then curing at 150° C. for 0.5-1 h, and finally cooling the cured glass fiber to room temperature to obtain a modified glass fiber;

[0066] S3, adding 50 parts of adipic acid, 50 parts of hexamethylenediamine and 0.1 parts of catalyst into the reaction kettle, heating to 240-260°C under nitrogen protection for polycondensation reaction, controlling the pressure in the kettle at 1-2MPa during the polycondensation reaction, the reaction time is 4-6h, and the generated water is continuously discharged; wherein the catalyst is ammonium dihydrogen phosphate;

[0067] S4. After the polycondensation reaction is completed, 10 parts of rubber toughening agent, 5 parts of nano-silicon dioxide, 3 parts of plasticizer, 8 parts of flame retardant and 2 parts of antioxidant are gradually added into the reaction kettle for blending. The blending time is 0.5h, the stirring speed is 50-100 rpm, and the temperature is maintained at 260°C-270°C; wherein the rubber toughening agent is polybutadiene, the plasticizer is phthalate, the flame retardant is aluminum hydroxide, and the antioxidant is tert-butyl hydroxytoluene;

[0068] S5, reacting the reaction materials in a multi-stage continuous reactor to obtain nylon 66;

[0069] S501, placing the reaction materials into the first reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.1-0.5MPa, the stirring speed is 50-100 rpm, and the reaction time is 0.5-1h;

[0070] S502, the reaction materials enter the second reaction unit of the reactor, the reaction temperature is 270°C-280°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 30-60 rpm, and the reaction time is 0.5-1h;

[0071] S503, the reaction materials enter the third reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 20-40 rpm, and the reaction time is 0.5-1h;

[0072] S6, heat-treating nylon 66, cooling, and pelletizing;

[0073] S701, keep nylon 66 between 180℃-200℃, and heat treatment for 1-2h;

[0074] S702, cooling the heat-treated nylon 66 to room temperature;

[0075] S703, after cooling, the nylon 66 is pelletized with a particle diameter of 3-5 mm.

[0076] The nylon 66 materials obtained in Example 1 and Example 2 were subjected to result verification tests, and the test results are shown in the following table:

[0077]

[0078]

[0079] In summary, the present invention achieves a comprehensive improvement in material performance by combining adipic acid, hexamethylenediamine, modified glass fiber, rubber toughening agent, nano-silica, plasticizer, flame retardant and antioxidant in a reasonable proportion and acting together in a nylon 66 matrix to form a synergistic effect between the components.

[0080] First, the modified glass fiber is surface-modified by γ-aminopropyltriethoxysilane coupling agent, and forms stable chemical bonds with the amino and carboxyl groups in the nylon 66 matrix during the polycondensation reaction. The formation of this chemical bond significantly enhances the interfacial bonding between the glass fiber and the nylon 66 matrix, reduces stress concentration at the interface, and thus improves the overall mechanical properties of the composite material, especially tensile strength and rigidity.

[0081] Secondly, the rubber toughening agent is evenly dispersed in the nylon 66 matrix during the blending process, forming a flexible network through physical block or chemical cross-linking. This flexible network can effectively absorb and disperse external stress when impacted, thereby significantly improving the toughness and impact resistance of the material and avoiding brittle fracture of the material under high load conditions.

[0082] At the same time, nano-silicon dioxide, with its high specific surface area and chemical activity, forms a uniform dispersion in the nylon 66 matrix and forms multi-point bonding with the matrix. This bonding not only effectively fills the microscopic defects inside the material, restricts the movement of polymer segments, improves the rigidity and wear resistance of the material, but also enhances the thermal stability of the material through synergistic effects, making it have better performance at high temperatures.

[0083] In addition, the introduction of plasticizers effectively reduces the glass transition temperature of nylon 66, improves the flexibility and processing fluidity of the material, and ensures a smooth and efficient process. Flame retardants significantly improve the flame retardancy of the material and slow down the flame propagation speed by combining with the molecular chain of nylon 66. Antioxidants play a role in capturing free radicals and inhibiting thermal oxidation reactions in the material, significantly extending the service life of the material and improving the stability and environmental performance of long-term use.

[0084] Through the synergistic effect of the above components, the present invention achieves comprehensive improvement in the mechanical properties, toughness, thermal stability, flame retardancy and processability of the nylon 66 composite material, effectively solves the problems existing in the performance and processing of traditional nylon 66 materials, and finally obtains a high-performance, environmentally friendly and safe nylon 66 composite material.

[0085] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A process for preparing nylon 66, characterized in that: The steps include: S1, taking adipic acid and hexamethylenediamine and drying them; S2, pre-treating the glass fiber, performing surface modification by using a coupling agent in a reaction kettle to obtain modified glass fiber; S3, adding adipic acid, hexamethylenediamine and a catalyst into a reaction kettle, and heating to 240-260° C. under nitrogen protection to carry out polycondensation reaction; S4. After the polycondensation reaction is completed, the rubber toughening agent, nano-silicon dioxide, plasticizer, flame retardant and antioxidant are gradually added into the reaction kettle for blending; S5, reacting the reaction materials in a multi-stage continuous reactor to obtain nylon 66; S6. Heat treat nylon 66, cool it, and pelletize it.

2. A process for preparing nylon 66 as claimed in claim 1, characterized in that: The ratio of adipic acid, hexamethylenediamine, modified glass fiber, rubber toughening agent, nano silicon dioxide, plasticizer, flame retardant, antioxidant and catalyst is: adipic acid: 50-55 parts, hexamethylenediamine: 45-50 parts, modified glass fiber: 20-30 parts, rubber toughening agent: 5-10 parts, nano silicon dioxide: 1-5 parts, plasticizer: 1-3 parts, flame retardant: 3-8 parts, antioxidant: 0.5-2 parts, catalyst: 0.1-0.5 parts.

3. A process for preparing nylon 66 as claimed in claim 1, characterized in that: The coupling agent is γ-aminopropyltriethoxysilane.

4. A process for preparing nylon 66 as claimed in claim 1, characterized in that: Step S2 also includes: S201, soaking the glass fiber in deionized water, stirring to remove dust and impurities on the surface, further cleaning with a neutral detergent to remove surface oil and other organic matter, and drying the cleaned glass fiber in an oven at 80-100° C. for 2-3 hours to ensure that the water is completely evaporated; S202, dissolving the coupling agent in 95% ethanol or deionized water at a mass ratio of 3-5%, adding a small amount of acetic acid to adjust the pH to 4-5, and mixing evenly; S203 completely immerses the glass fiber in the coupling agent solution for 0.5-1h to ensure that the fiber surface is completely covered by the coupling agent; S204, drying the impregnated glass fiber at 80-120°C for 1-2h, then curing at 150°C for 0.5-1h, and finally cooling the cured glass fiber to room temperature to obtain modified glass fiber.

5. A process for preparing nylon 66 as claimed in claim 1, characterized in that: In step S3, during the polycondensation reaction, the pressure in the autoclave is controlled at 1-2 MPa, the reaction time is 4-6 h, and the generated water is continuously discharged.

6. A process for preparing nylon 66 as claimed in claim 1, characterized in that: Step S4 also includes: first adding a rubber toughening agent, then adding nano silicon dioxide, a plasticizer, a flame retardant and an antioxidant in sequence, and slowly adding them within 1-5 minutes.

7. A process for preparing nylon 66 as claimed in claim 1, characterized in that: In step S4, the blending time is 0.5 h, the stirring speed is 50-100 rpm, and the temperature is maintained at 260° C.-270° C.

8. A process for preparing nylon 66 as claimed in claim 1, characterized in that: Step S5 also includes: S501, placing the reaction materials into the first reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.1-0.5MPa, the stirring speed is 50-100 rpm, and the reaction time is 0.5-1h; S502, the reaction materials enter the second reaction unit of the reactor, the reaction temperature is 270°C-280°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 30-60 rpm, and the reaction time is 0.5-1h; S503, the reaction materials enter the third reaction unit of the reactor, the reaction temperature is 260°C-270°C, the reactor pressure is 0.05-0.1MPa, the stirring speed is 20-40 rpm, and the reaction time is 0.5-1h.

9. A process for preparing nylon 66 as claimed in claim 1, characterized in that: Step S6 also includes: S701, keep nylon 66 between 180℃-200℃, and heat treatment for 1-2h; S702, cooling the heat-treated nylon 66 to room temperature; S703, after cooling, the nylon 66 is pelletized with a particle diameter of 3-5 mm.